Enhanced Cyclic Stability of LiNi0.815Co0.15Al0.035O2 Cathodes by Surface Modification with BiPO4 for Applications in Rechargeable Lithium Polymer Batteries. Issue 15 (5th August 2021) - Meghnani, Dipika; Gupta, Himani; Singh, Shishir K.; Srivastava, Nitin; Mishra, Raghvendra; Tiwari, Rupesh K.; Patel, Anupam; Tiwari, Anurag; Singh, Rajendra K.
Abstract: The effect of incorporating the ionic liquid (IL) N‐methyl‐N‐propyl piperidinium bis(fluorosulfonyl)imide (PP13 FSI) to a polymer electrolyte (PE) based on the polymer poly(ethylene oxide) (PEO)‐ lithium bis(fluorosulfonyl)imide (LiFSI) [PEO+20 wt.% LiFSI] is investigated. The concentration of PP13 FSI IL is varied from 10 to 40 wt.% in the PEO+20 wt.% LiFSI system and the influences of the ionic conductivity, thermal stability, diffusion coefficient, and electrochemical stability are studied. The 40 wt.% IL containing PE shows good thermal stability ∼210 °C and high ionic conductivity, 1 . 06 × 10 - 3 S . c m - 1, at 40 °C with a wide electrochemical stability window ∼4.7 V vs. Li/Li + and high D L i + ∼ 1 . 25 × 10 - 7 c m 2 . s - 1 at 30 °C. Furthermore, the electronic conducting BiPO4 is coated on the LiNi0.815 Co0.15 Al0.035 O2 (BiPO4 @NCA) cathode by the liquid precipitation method. To investigate the structural and electrochemical properties of the pristine and BiPO4 @NCA cathodes, XRD, SEM, TEM, and DSC as well as the electrochemical method are employed. The XRD results reveal a hexagonal layered structure without any impurity phase in BiPO4 @NCA. The TEM investigations show that the BiPO4 layer (∼10 nm) is homogeneously coated on the NCA particles. The electrochemical testing showed an improvement in the cyclic performance of BiPO4 @NCA with a capacity retention 94.64 % after 150 cycles, which is 8 % greater than that of the pristine NCA. Abstract : A BiPO4 ‐coated lithium nickel cobalt aluminum oxide (NCA) based cathode (BiPO4 @NCA) is synthesized by the liquid precipitation method. The effect of the BiPO4 coating on the electrochemical performance is investigated. The coating prevents the rogue reaction, enhances the kinetics of lithium ions, improves the structural stability, and thus provides a long‐term cyclic stability compared to pristine NCA.